Moral Intelligence Of First-Year Primary School Students Enrolled And Not Enrolled In Kindergarten (Journal of the College of Basic Education, 2024)
The current research aims to identify the moral intelligence of first-grade primary school students enrolled and not enrolled in kindergartens. The research sample amounted to (60) male and female students enrolled and not enrolled in kindergartens affiliated with the General Directorate of Education of Baghdad, Al-Karkh, third for the academic year (2023/2024). To achieve the goal, the research used a scale. (Waryoush 2015), which consists of seven areas and 31 items. To achieve the results, statistical methods (s.p.s.s) were used. The results of the research were for the benefit of first-year primary school students enrolled in kindergarten.